Ecm29-Dependent Proteasome Localization Regulates Cytoskeleton Remodeling at the Immune Synapse - Ibañez-Vega, Jorge; Del Valle, Felipe; Sáez, Juan José; Guzman, Fanny; Diaz, Jheimmy; Soza, Andrea; Yuseff, María Isabel (Frontiers in Cell and Developmental Biology, 2021)
The formation of an immune synapse (IS) enables B cells to capture membrane-tethered antigens exposed on antigen-presenting cells. This process relies on actin remodeling at the plasma membrane and at the perinuclear region, which promotes cell spreading and allows the recruitment of the centrosome together with lysosomes to the immune synapse, to facilitate antigen extraction. How B cells manage to synchronize actin rearrangements between these cellular domains remains poorly understood. We report here that the proteasome adaptor protein, Ecm29, regulates the localization of the proteasome between the centrosome and the cell cortex of B cells, to control local actin remodeling. Silencing Ecm29 leads to an accumulation of the proteasome at the IS of B cells, which reduces actin polymerization rates at this level, decreasing actin retrograde flow in lamellipodia and enhancing the spreading response elicited by B cells upon encounter with immobilized antigens. Moreover, lower levels of proteasome within the perinuclear region of Ecm29-silenced cells results in the accumulation of F-actin at the centrosome, which impairs centrosome and lysosome repositioning to the synapse leading to defective antigen extraction and presentation. Overall, our findings support a model where B cell polarization relies on the asymmetric distribution of the proteasome, mediated by Ecm29, which coordinates actin dynamics at the centrosome and the IS, promoting lysosome recruitment and cell spreading.